Nilai-Nilai Spiritualitas Pendidikan Islam dalam Novel “Imama Al-Hafidzh” Karya Tri Lyagustina - Awin Setyaningsih; Faisal Kamal; Fatiatun Fatiatun (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2025)
Islamic education does not merely focus on the transfer of knowledge but also emphasizes the development of character, morality, and spiritual consciousness. Spiritual values are central in shaping learners who are not only intellectually capable but also faithful and pious. In this context, teachers serve not only as educators but also as spiritual mentors who instill values such as sincerity (ikhlas), trust in God (tawakkal), and divine awareness. This study aims to: 1) Explore the content and themes of the novel Imama Al-Hafidzh by Tri Lyagustina; and 2) Identify the Islamic spiritual values present in the novel and their relevance to contemporary life. This research employs a qualitative approach using library research methods, relying on both primary and secondary sources. Data analysis was conducted by collecting, comparing, and synthesizing information to produce a systematic and comprehensive study. The findings reveal that the novel tells the story of a young man who burns his own finger in a forest to resist temptation, symbolizing strong faith and self-control. The novel conveys messages such as steadfastness in principles, resisting worldly pleasures, not neglecting worship, and making the most of life to serve Allah. The spiritual values found in the novel include: faith, sincerity, patience, trust in God, gratitude, acceptance, repentance, Islamic brotherhood, asceticism, positive thinking, humility in worship, consistency, and love. These values, which are rooted in the Qur’an and Hadith, are highly relevant and can be integrated into Islamic religious education to strengthen students' character in the face of modern challenges.